2021
DOI: 10.1111/jade.12358
|View full text |Cite
|
Sign up to set email alerts
|

Art Education and Development Cooperation: A Project in Educational Centres for Children with Special Needs in India

Abstract: The purpose of this article is to examine Art Education and Human Development, a development cooperation project carried out during the period 2015-2018 in Ananthapuramu, India and implemented between the University of Seville, Spain and the Fundaci on Vicente Ferrer (Vicente Ferrer Foundation) -Rural Development Trust (FVF-RDT). Drawing on action research methods, the participants were children with disability and resident teachers, in accordance with the schools involved in the study. The aim of our work was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This theme examines the impact of children and adolescents' "participation" in education on their "achievement" and holistic development. It highlights the importance of active involvement of children and adolescents in academic, social, and emotional development [47], particularly for "out-of-school youth" [48]. The theme explores diversity and inclusivity in educational practices, emphasizing strategies adaptable to students of different ages and backgrounds [49].…”
Section: Research Theme 7: Child Development and Educational Particip...mentioning
confidence: 99%
“…This theme examines the impact of children and adolescents' "participation" in education on their "achievement" and holistic development. It highlights the importance of active involvement of children and adolescents in academic, social, and emotional development [47], particularly for "out-of-school youth" [48]. The theme explores diversity and inclusivity in educational practices, emphasizing strategies adaptable to students of different ages and backgrounds [49].…”
Section: Research Theme 7: Child Development and Educational Particip...mentioning
confidence: 99%
“…This blended teaching method can effectively enhance the cultivation of artistic talents in Kenya and provide sustainable development of artistic talents in society. Literature [8] analyzed the training of art teaching in India and concluded that art education can help human development and can be a tool for social transformation, providing a reference for art practice and the enhancement of human values. Literature [9] asserts that arts education is a cognitive choice and that cognition is crucial to the value of arts education.…”
Section: Review Of Related Work Studiesmentioning
confidence: 99%
“…Aiming at the advantages of network multimedia with sharing function and caching function in teaching content, network multimedia technology is used in art education, which can greatly improve the teaching effect of art education. The main application of multimedia technology in art education is shown in Figure 2, which mainly includes three major contents, namely, user management, course content management, content sharing and caching [29][30]. The user module is mainly used to manage user information, perform user registration and login, as well as allow system administrators to modify and delete users and perform other functions.…”
Section: Application Of Network Multimedia Technology In Art Educationmentioning
confidence: 99%